2018
DOI: 10.1111/jbfa.12353
|View full text |Cite
|
Sign up to set email alerts
|

Employee‐friendly practices, product market competition and firm value

Abstract: In this paper, we examine whether employee‐friendly practices are associated with product market competition, and whether firm value is related to employee‐friendly practices and product market competition. Using a large sample of US firms, we find positive and significant associations between employee friendliness and product market competition, and between firm value and employee friendliness when product market competition is high, consistent with the value creation theory. Both positive relations hold when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 102 publications
2
21
0
Order By: Relevance
“…The positive values of the mean, median and significance of the match-adjusted variables in the Faleye and Trahan (2011) study, as summarized in the latter statistics compiled for this paper, yielded interesting implications when compared with the Chang and Jo (2019) research. All four measures of value among the Fortune best companies outperformed their matched pairs in Faleye and Trahan.…”
Section: Analysis Of the Four Measures Of Valuementioning
confidence: 68%
See 4 more Smart Citations
“…The positive values of the mean, median and significance of the match-adjusted variables in the Faleye and Trahan (2011) study, as summarized in the latter statistics compiled for this paper, yielded interesting implications when compared with the Chang and Jo (2019) research. All four measures of value among the Fortune best companies outperformed their matched pairs in Faleye and Trahan.…”
Section: Analysis Of the Four Measures Of Valuementioning
confidence: 68%
“…All four measures of value among the Fortune best companies outperformed their matched pairs in Faleye and Trahan. However, from the statistical perspective of central tendency, the sample in Faleye and Trahan’s study shows that the firms tend to be undervalued, whereas Chang and Jo’s (2019) research revealed a centrally overvalued sample of firms. Faleye and Trahan’s sample was from 1998 to 2005, an eight-year period, whereas Chang and Jo’s sample was from 1991 to 2012 or two decades.…”
Section: Analysis Of the Four Measures Of Valuementioning
confidence: 91%
See 3 more Smart Citations